Test-Retest-Reliability of Video-Oculography During Free Visual Exploration in Right-Hemispheric Stroke Patients With Neglect - Kaufmann, Brigitte Charlotte; Cazzoli, Dario; Müri, René Martin; Nef, Tobias; Nyffeler, Thomas (Frontiers in Neuroscience, 2020)
Mean gaze position during free visual exploration (FVE) is a sensitive tool to detect neglect in patients after right-hemispheric stroke. Here we investigated the test-retest-reliability of mean gaze position during FVE in 23 patients with left-sided neglect after a first-ever sub-acute right hemispheric stroke. We analysed the reliability between different test sets administered within eleven days (test sets A and B, each including different images and their mirrored versions), and between repeated measures using the same test set administered three times within two days (test set C, including the same images and their mirrored versions). The Intra-Class Correlation coefficient (ICC) showed good reliability between the two different test sets (test sets A and B; ICC =.819), and excellent reliability for the repeated measures with the same test set C (ICC=.964). FVE can therefore be recommended for the longitudinal assessments of patients' neglect severity during neurorehabilitation as well as in treatment trials.